2019
DOI: 10.5194/amt-12-4779-2019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of n-alkanes, polycyclic aromatic hydrocarbons and hopanes in atmospheric aerosol: evaluation and comparison of thermal desorption GC-MS and solvent extraction GC-MS approaches

Abstract: Abstract. Organic aerosol (OA) constitutes a large fraction of fine particulate matter (PM) in the urban air. However, the chemical nature and sources of OA are not well constrained. Quantitative analysis of OA is essential for understanding the sources and atmospheric evolution of fine PM, which requires accurate quantification of some organic compounds (e.g., markers). In this study, two analytical approaches, i.e., thermal desorption (TD) gas chromatography mass spectrometry (GC-MS) and solvent extract (SE)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In this study, 75-155 CHOS-compounds were observed, accounting for 10 %, 12 % and 14 % of the total peak abundance of all organics in Changchun-, Shanghai-and Guangzhou-, respectively. Around 89 %-96 % of these CHOS-compounds were found to fulfill the O/S ≥ 4 criterion allowing the assignment of at least one -OSO 3 H functional group and thus a tentative classification to organosulfates (OSs) (Lin et al, 2012a, b;Tao et al, 2014;Wang et al, 2016Wang et al, , 2017Wang et al, , 2018Wang et al, , 2019a. OSs were shown to affect the surface activity and hygroscopic properties of the aerosol particles, leading to potential impacts on climate (Hansen et al, 2015;Wang et al, 2019a).…”
Section: Chos-compoundsmentioning
confidence: 99%
“…In this study, 75-155 CHOS-compounds were observed, accounting for 10 %, 12 % and 14 % of the total peak abundance of all organics in Changchun-, Shanghai-and Guangzhou-, respectively. Around 89 %-96 % of these CHOS-compounds were found to fulfill the O/S ≥ 4 criterion allowing the assignment of at least one -OSO 3 H functional group and thus a tentative classification to organosulfates (OSs) (Lin et al, 2012a, b;Tao et al, 2014;Wang et al, 2016Wang et al, , 2017Wang et al, , 2018Wang et al, , 2019a. OSs were shown to affect the surface activity and hygroscopic properties of the aerosol particles, leading to potential impacts on climate (Hansen et al, 2015;Wang et al, 2019a).…”
Section: Chos-compoundsmentioning
confidence: 99%
“…Phthalates are analyzed by gas chromatography/mass spectrometry (GC/MS) after solvent extraction using tetrahydrofuran, hexane, or methanol 17–19 . Although it is a widely used method worldwide because of its high accuracy, it is problematic in that it uses solvents that are destructive to our environment 20,21 . Therefore, developing an analytic method that reduces the burden imposed on the environment is needed.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Although it is a widely used method worldwide because of its high accuracy, it is problematic in that it uses solvents that are destructive to our environment. 20,21 Therefore, developing an analytic method that reduces the burden imposed on the environment is needed. According to the principles of green analytical chemistry 22,23 and green sample preparation, 24 direct analysis is preferred to avoid sample treatment, and it is better to minimize samples, chemicals, and wastes.…”
mentioning
confidence: 99%
“…The necessity of monitoring of PAHs in air explains the proof of the use much more effective analytical methods enabling their identification in a manner as simple and fast as possible. Among the most frequently applied modern methods of analysis of aromatic hydrocarbons in environmental samples are the chromatographic ones, particularly capillary gas chromatography, the most effective with mass spectrometry as the tool of detection (GC and GC-MS methods) [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%